2012
DOI: 10.1128/jvi.01126-12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Intracellular Trafficking of Epstein-Barr Virus BBLF1, a Protein Involved in Virion Maturation

Abstract: Epstein-Barr virus (EBV) BBLF1 shares 13 to 15% amino acid sequence identities with the herpes simplex virus 1 UL11 and cytomegalovirus UL99 tegument proteins, which are involved in the final envelopment during viral maturation. This study demonstrates that BBLF1 is a myristoylated and palmitoylated protein, as are UL11 and UL99. Myristoylation of BBLF1 both facilitates its membrane anchoring and stabilizes it. BBLF1 is shown to localize to thetrans-Golgi network (TGN) along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 46 publications
4
56
1
Order By: Relevance
“…Cells were fixed with 4% paraformaldehyde and processed for indirect immunofluorescence staining, which was conducted using a primary antibody against Flag (Sigma), BBLF1 (Chiu et al, 2012), or BGLF2, following incubation with fluorescently labeled secondary antibodies (Invitrogen). Mouse anti-BGLF2 monoclonal antibody was generated using the synthesized peptide 145 KTVEELQDITPS 155 (Abmart, China).…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…Cells were fixed with 4% paraformaldehyde and processed for indirect immunofluorescence staining, which was conducted using a primary antibody against Flag (Sigma), BBLF1 (Chiu et al, 2012), or BGLF2, following incubation with fluorescently labeled secondary antibodies (Invitrogen). Mouse anti-BGLF2 monoclonal antibody was generated using the synthesized peptide 145 KTVEELQDITPS 155 (Abmart, China).…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…This viral mimicry (see Davey et al, 2011) enables the viruses to assemble progeny, escape immune surveillance and prevent apoptosis. For example, PACS-1 binds to acidic clusters in the human cytomegalovirus (HCMV) envelope glycoprotein gB and the Epstein-Barr virus (EBV) tegument protein BBLF1 and localizes them to the TGN to support virus assembly Chiu et al, 2012) (see Fig. 3A).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of functional data regarding the herpesvirus tegument comes primarily from research on alpha-and betaherpesviruses, which has shown that tegument proteins function in crucial roles in viral replication, including transcytosis of the herpesvirus capsid toward the nucleus during initial infection and egress from the nucleus toward the periphery during lytic replication (12,(36)(37)(38)(39). Additional functions of tegument proteins modulate the host cell environment during the immediateearly phase of infection (40), including shutoff of host gene expression (21,41,42), antagonism of the innate antiviral host response (43)(44)(45)(46)(47), and assembly and egress of herpesvirus virions (38,(48)(49)(50); reviewed in reference 51).…”
mentioning
confidence: 99%